THE ROLE OF PERFORMANCE FEEDBACK QUALITY TO REDUCE THE PROPENSITY TO CREATE BUDGETARY SLACK AT PRIVATE UNIVERSITY - Rismayanti, Febriana Dwi; Lembut, Putu Indrajaya; Wijayanti, Dian (Jurnal Aplikasi Manajemen, 2018)
This study aims to test hypotheses developed by Lavengin and Mendoza (2013). This study aims to investigate the positive effect of performance feedback quality on perceived procedural justice and perceived interactional justice. Furthermore, this study investigated the negative effect of perceived procedural justice and perceived interactional justice on a propensity to create budgetary slack with trust in the supervisor as a mediating variable. This study uses a survey method via questionnaire, with middle and lower manager who participate in preparing a budget at Private University as respondent. The results show that performance feedback quality can increase perceived procedural justice and perceived interactional justice. Furthermore, this study can not prove that perceived procedural justice and perceived interactional justice can reduce the propensity to create budgetary slack through trust in supervisor. Nevertheless, the results can prove that perceived interactional justice can reduce the propensity to create budgetary slack, that means the relationship between perceived interactional justice and propensity to create budgetary slack is a direct relationship. The results also show that interactional justice can increase trust in the supervisor. Overall, this study can prove the hypotheses developed by Langevin and Mendoza (2013), that management control systems can reduce a manager’s unethical behavior.